Smart Product Counter / Fitri Al-Ibni Nadzri and Shahrul Hisham Samsudin - Nadzri, Fitri Al-Ibni; Samsudin, Shahrul Hisham (2003)
This is one of those useful little projects intended for use in our life to make it easier for human beings. We called our project ‘SMART PRODUCT COUNTER', rhis project is used to count goods automatically. The purpose of this project is to develop our skills in research, design and creating a useful project for human things. In this project we are using LDR (light detected resistor) circuit as a sensor to sense goods and the counter circuit will count the goods. We also were using a timer circuit and motor circuit for our project. The main purpose of our project is to count goods by automatically. For the first part, the goods will place on the conveyer belt. To move the conveyer belt a start button has been put at the starting point of the conveyer belt. Once the start button is push it will ‘on’ the timer circuit to count for a certain period of time. This timer circuit is connected to motor to pull the conveyer belt. The second part, the sensor is place at the end of the conveyer belt. This sensor circuit is used to sense any goods past through a dark box. This sensor circuit is connected to the counter circuit to count the goods as one goods.